Road and rail traffic noise induce comparable extra-aural effects as revealed during a short-term memory test - Eugen Gallasch; Reinhard B Raggam; Michael Cik; Jasmin Rabensteiner; Andreas Lackner; Barbara Piber; Egon Marth (Noise and Health, 2016)
To examine extraaural effects as induced by 20 min of road (ROAD) and 20 min of rail (RAIL) traffic noise with same loudness (75 dBA), a laboratory study was carried out. The study (N = 54) consisted of 28 high and 26 low-annoyed healthy individuals as determined by a traffic annoyance test. To control attention, all individuals performed a nonauditory short-term memory test during the noise exposures. A within-subject design, with phases of ROAD, RAIL, and CALM (memory test only), alternated by phases of rest, was defined. Heart rate (HR), systolic blood pressure (sBP), total peripheral resistance (TPR), as well as three autonomic variables, preejection period (PEP), 0.15–0.4 Hz high-frequency component of HR variability (HF), and salivary stress biomarker alpha amylase (sAA) were measured. In relation to CALM, HR increased (RAIL +2.1%, ROAD +2.5%), sBP tended to increase against the end of noise exposure, PEP decreased (RAIL −0.7%, ROAD −0.8%), HF decreased (RAIL −3.4%, ROAD −2.9%), and sAA increased (RAIL +78%, ROAD +69%). No differences were found between RAIL and ROAD, indicating that both noise stressors induced comparable extraaural effects. Factor annoyance showed significant during CALM. Here a reduced sympathetic drive (higher PEP values) combined with an increased vascular tone (higher TPR values) was found at the high-annoyed subgroup.